Béton et utopie avant 1914 : architecture et « moule social » - Baridon, Laurent (RACAR : Revue d'art canadienne / Canadian Art Review)

(untitled) (UAAC-AAUC (University Art Association of Canada | Association d'art des universités du Canada), 2006)
The utopian reformers of the nineteenth century, while they describe houses and towns, seem to have mistrusted the architects who hoped to materialize them. Those who did try were either ostracized or blamed for the repeated failures of the projects. This can be explained by the misunderstandings that were bound to appear between the ambiguities of utopian thought and the positive, heuristic character of architectural design. The problem raised by the actual building of edifices was ignored by the utopians, while the architects and the urbanists saw it as a sine qua non.Victor Considérant, by coining the concept of feasibility (“réalisabilité”), opened the way to the construction of J.B.A. Godin’s Familistère. To attain “harmony,” the architect had to conceive a “social mould,” as Victor Calland said, which was to modify human beings biologically. Concrete, a building material popularized by François Coignet, a disciple of Fourier’s, embodied this new hope founded on architecture. Inexpensive and malleable, it seemed suitable for the building of edifices whose organic character was designed to promote the transformation of the individual and of the society striving for perfection.